Motor coordination, working memory, and academic achievement in a normative adolescent sample: Testing a mediation model - Rigoli, Daniela; Piek, Jan Patricia; Kane, Robert; Oosterlaan, J. (Elsevier, 2012)
The aim of the present study was to examine whether the relationship between motor coordination and academic achievement is mediated by working memory (WM) in a normative adolescent sample. Participants included 93 adolescents aged 12–16. The Movement Assessment Battery for Children-2 provided three indicators of motor coordination (Manual Dexterity, Aiming and Catching, and Balance), the WM Index of the Wechsler Intelligence Scale for Children-IV and the N-back paradigm provided two indicators of WM, and the Wechsler Individual Achievement Test-II provided three indicators of academic achievement (Word Reading, Spelling, and Numerical Operations). Structural equation modeling, controlling for verbal comprehension, attention deficit hyperactivity disorder symptoms, and socioeconomic status, suggested that the association between motor coordination and academic achievement may be best understood in terms of a mechanism whereby motor coordination (specifically, Aiming and Catching skills) has an indirect impact on academic outcomes via WM. These findings have important implications for the assessment and treatment of motor coordination and learning difficulties as well as in increasing the understanding of the possible neural mechanisms underpinning the relationship between these areas.